Bioactivities of serotonin transporter mediate antidepressant effects of Acorus tatarinowii Schott. (15th September 2019) - Zhang, Feng-Hong; Wang, Zhi-Mei; Liu, Yan-Ting; Huang, Ji-Sheng; Liang, Shuang; Wu, Hong-Hua; Xu, Yan-Tong
Abstract: Ethnopharmacological relevance: Acrorus tatarinowii Schott has been widely used in the treatments of neuropsychiatric and digestive disorders in clinical practices of traditional Chinese medicine for thousands of years. Both clinical and preclinical studies demonstrated antidepressant effects of A. tatarinowii . However, the possible action mechanisms of antidepressant effects of A. tatarinowii remain unraveled. Aim of the study : The present study aimed to investigate the roles of serotonin transporter (SERT) in antidepressant effects of A. tatarinowii . Materials and methods: Antidepressant effects of water extract of A. tatarinowii were evaluated by forced swimming test (FST), tail suspension test (TST) and locomotor activity test. The water extract was analyzed by ultra high performance liquid chromatography (UPLC) method. Two major fractions of A. tatarinowii, petroleum ether extract and water extract after petroleum ether processed, were prepared and analyzed by UPLC method. Further, volatile oil extracted by ether extraction, solid phase micro-extraction (SPME) and hydro-distillation were compared and analyzed by gas chromatography-mass spectrometer (GC-MS) method. Finally, major constituents of water extract of A. tatarinowii were isolated by preparative high performance liquid chromatography (HPLC) and identified by extensive spectroscopic analyses. Effects of all of the above mentioned samples on SERT activity were tested by a high content assay (HCA). Results: Results of FST, TST and locomotor activity confirmed that water extract of A. tatarinowii significantly decreased mice immobility time but did not change mice locomotor activity. UPLC analysis results revealed that the water extract contained trace amount of β -asarone (0.0004206%) and α -asarone (0.0001918%). HCA results demonstrated that the water extract significantly enhanced SERT activity at 100 μ g/mL. Further, GC-MS and UPLC analyses revealed that petroleum ether extract contained high content of β -asarone (45.63%) and α -asarone (12.50%). GC-MS analysis results demonstrated that the volatile oil extracted by ether extraction, SPME and hydro-distillation contained similar major components. HCA results verified that the petroleum ether extract significantly enhanced SERT activity at 1.56 μ g/mL. Moreover, UPLC analysis of water extract after petroleum ether processed did not show any characteristic peaks. HCA results demonstrated that this extract significantly inhibited SERT activity at 50–100 μ g/mL. Finally, phytochemistry investigation on the water extract of A. tatarinowii afforded seven constituents including veratric acid (9 ), anisic acid (7 ), 3, 4, 5-trimethoxybenzoic acid (3 ), trans -isoferulic acid (2 ), 2, 4, 5-trimethoxybenzoic acid (11 ), 4-hydroxybenzoic acid (6 ) and syringic acid (13 ). Their structures were established on the basis of nuclear magnetic resonance (NMR) and mass spectrometer (MS) data and comparative UPLC analyses. HCA results demonstrated the major components of the water extract of A. tatarinowii demonstrated SERT enhancement/inhibition activities. Conclusions: This study first systematically demonstrated the roles of SERT activity in antidepressant effects of A. tatarinowii, including water extract, major fractions and main constituents. These results revealed that A. tatarinowii could regulate SERT activities in bidirectional ways. Graphical abstract: Serotonin transporters play important roles in antidepressant effects of Acorus tatarinowii .Image 1